Investigation of a Late‐Stage Derivatization Approach to Isatogens: Discovery of New Reaction Pathways. Issue 1 (17th November 2015) - Edeson, Steven J.; Maduli, Elvis J. M.; Swanson, Stephen; Procopiou, Panayiotis A.; Harrity, Joseph P. A.
Abstract: We have developed a new strategy for preparing 2‐substituted indolone N ‐oxides (isatogens) by substitution reactions with aryl‐ and alkyl‐organometallic reagents. This approach allows a range of substituents to be incorporated at a late stage and complements existing methods that necessitate their early stage incorporation during substrate preparation. Further chemistry has been found to take place at the nitrone moiety; intramolecular dipolar cycloaddition provides access to angularly fused tricyclic heterocycles. More unusually however, these compounds are prone to further addition by organozinc reagents leading to 2, 2‐disubstituted 3‐oxindole products. Abstract : Take your pick. 2‐Iodoisatogens represent readily accessible precursors to a range of 3‐oxindole products. Specifically, 2‐aryl‐ and 2‐alkyl‐isatogens, as well as N ‐alkoxy 2, 2‐disubstituted 3‐oxindoles and angularly fused heterocycles can all be prepared by judicious choice of a Zn‐based organometallic reagent.